PERSEPSI DAN PERILAKU MASYARAKAT TERHADAP AIR LIMBAH YANG DIHASILKAN DAN KUALITAS AIR TUKAD RANGDA, KOTA DENPASAR, PROVINSI BALI - Priantari, Ni Luh Putu Mega; Budiarsa Suyasa, I Wayan; Windia, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2017)
Many activities and the continuous disposal of waste water has resulted water pollution in Tukad Rangda. Tukad Rangda's water quality over the last five years (2012-2016) indicated experiencing contamination with decreasing water quality. The condition indicates the need of serious effort to maintain the water quality of Tukad Rangda. The purpose of this research is to know the perception and behavior of head of household and businesses in conducting waste water management that potentially causing Tukad Rangda water contamination, determining water quality and water quality status based on the Pollution Index, and determining appropriate alternative strategies to control water pollution in Tukad Rangda. Sample was collected by purposive sampling. Water samples was taken at three point: on the upstream, middle, and downstream of Tukad Rangda. Samples are analyzed in situ and in laboratory. Determination of perception and community behavior based on questionnaires and interviews to households and businesses. The data obtained were analyzed by force-field analysis to determine alternative strategy of Tukad Rangda water contamination control. The results of perception analysis of households and businesses on waste water management that has the potential to cause Tukad Rangda water contamination shows well-categorized results. However, for the behavior of head of households and businesses on waste water management that potentially causing Tukad Rangda water pollution, each of them showing results that can be categorized as quite good and less good respectively. Water quality of Tukad Rangda at upstream, middle, and downstream areas have exceeded the water quality standard class II in accordance with the Bali Governor Regulations No. 16 year 2016 for these parameters: BOD, COD, phosphate, and lead. Water quality status of Tukad Rangda based on Method of Pollution Index at upstream, middle, and downstream classified slightly contaminated. Based on force-field analysis, the alternative strategy obtained is increasing the insight and understanding about waste water management to the community, water waste management regulation at household scale, coaching, supervision, and law enforcement against businesses violating the applicable regulations, providing waste water treatment facilities, as well as the development of Tukad Rangda as water tourism area through the involvement of community participation.